Epigenetic inactivation of TRAIL decoy receptors at 8p12‐21.3 commonly deleted region confers sensitivity to Apo2L/trail‐Cisplatin combination therapy in cervical cancer. Issue 2 (6th November 2015) - Narayan, Gopeshwar; Xie, Dongxu; Ishdorj, Ganchimeg; Scotto, Luigi; Mansukhani, Mahesh; Pothuri, Bhavana; Wright, Jason D.; Kaufmann, Andreas M.; Schneider, Achim; Arias‐Pulido, Hugo; Murty, Vundavalli V.
Abstract : Multiple chromosomal regions are affected by deletions in cervical cancer (CC) genomes, but their consequence and target gene involvement remains unknown. Our single nucleotide polymorphism (SNP) array identified 8p copy number losses localized to an 8.4 Mb minimal deleted region (MDR) in 36% of CC. The 8p MDR was associated with tumor size, treatment outcome, and with multiple HPV infections. Genetic, epigenetic, and expression analyses of candidate genes at MDR identified promoter hypermethylation and/or inactivation of decoy receptors TNFRSF10C and TNFRSF10D in the majority of CC patients. TNFRSF10C methylation was also detected in precancerous lesions suggesting that this change is an early event in cervical tumorigenesis. We further demonstrate here that CC cell lines exhibiting downregulated expression of TNFRSF10C and/or TNFRSF10D effectively respond to TRAIL‐induced apoptosis and this affect was synergistic in combination with DNA damaging chemotherapeutic drugs. We show that the CC cell lines harboring epigenetic inactivation of TRAIL decoy receptors effectively activate downstream caspases suggesting a critical role of inactivation of these genes in efficient execution of extrinsic apoptotic pathway and therapy response. Therefore, these findings shed new light on the role of genetic/epigenetic defects in TRAIL decoy receptor genes in the pathogenesis of CC and provide an opportunity to explore strategies to test decoy receptor gene inactivation as a biomarker of response to Apo2L/TRAIL‐combination therapy. © 2015 Wiley Periodicals, Inc.